Cofinancing in Environment and Development : Evidence from the Global Environment Facility - Kotchen, Matthew J.; Negi, Neeraj Kumar (Published by Oxford University Press on behalf of the World Bank, 2020)
Leveraged cofinancing has emerged as a policy priority among international environment and development agencies. We study the determinants and impacts of cofinancing using a comprehensive data set from the GEF on 3,269 projects from 1991 through 2014, along with detailed ex post evaluations of more than 650 completed projects. We find that greater emphasis on cofinancing will tend to favor projects that are larger, less global in reach, focused on climate change, in countries with better governance, and led by certain multilateral development banks. A push towards more private sector involvement and loans, rather than grant financing, will tend to encourage projects with similar characteristics. Greater cofinancing results in better ex post evaluations, but projects executed by the private sector tend to achieve lower ratings. The results provide insight into how agencies can promote cofinancing and into how greater emphasis on cofinancing, private sector involvement, and nongrant instruments may implicitly shift environment and development priorities, as well as project outcomes.